A modified algorithm for aiming point guidance law - Chen, Chuen-Ming; Chou, Ching-Lain; Tsao, Lu-Ping; Chen, Chi-Teh (International journal of systems science, 2000)
This work presents a modified algorithm for improving the intercept performance of the Aiming Point Guidance (APG) law (Tsao et al. 1998) subject to the dynamic lags of a missile system. The performance of APG is improved by taking into account the motions of the collision course and the achieved missile turning rate. Numerical simulations show that the modified APG (MAPG) performs better than the APG in terms of miss distance, interception time, and lateral acceleration demand.